Photonic Approach for Measuring AOA of Multiple Signals With Improved Measurement Accuracy - Hao Chen; Chongjia Huang; Erwin H. W. Chan (IEEE Photonics Journal)
The objective of this paper is to present a microwave photonic system that can measure the angle of arrival (AOA) of multiple microwave signals with improved measurement accuracy. It is based on a photonic mixer approach to down convert the incoming microwave signals into IF signals, which enables a low-frequency electrical spectrum analyser to be used for measuring the power of the IF signals to determine the incoming microwave signal AOAs. AOA measurement errors can be reduced by operating the optical modulator at a different transmission point for a different range of microwave signal AOA. The system also has the ability to remove the incoming microwave signal amplitude dependence in the AOA measurement. Measured results demonstrate 0°−81.5° AOA measurement with less than ±2° errors over the 0°−30° and 30°−81.5° AOA measurement range when the optical modulator is biased at the minimum and maximum transmission point respectively. The errors remain below ±2° even when there is a ±0.1 dB change in the output IF signal power. AOA measurement of two microwave signals is also demonstrated.